Optical and photoluminescence spectroscopy analysis and Doppler broadening annihilation radiation studies of perovskites based on La1-XNiXMnO2.75 thin layers - YUMAK YAHŞİ, AYŞE; TAV, CUMALİ; YAHŞİ, UĞUR (ELSEVIER GMBH, 2020)
In this work, perovskite La1-xNixMnO2.75 (with x = 0, 0.1, 0.2, 0.3 and 0.4) is synthesized by spray pyrolysis route at 460 degrees C. X-ray pattern analysis showed orthorhombic structure of the pure and Ni-doped. Based on X-ray analysis interesting parameters are then extracted such as crystallite size, micro-strain (epsilon) and dislocation density (delta). A high transmittance coefficient at 76 % and the optical band gap varies from 2.33 to 2.85 eV are revealed by the spectroscopy analysis. The Urbach energy varies from 273 to 381.7 meV. Furthermore, refractive index, extinction coefficient, and dielectric constants versus photon wavelength are plotted for pure and Ni-doped LaMnO2.75 layers. PL measurements analysis describe peaks within violet, blue, and green emission ranges. Finally, Doppler-broadening energy studies have been performed to investigate the defect structural evolution in polycrystalline La1-xNixMnO2.75. The studies derived S, R and W parameters are used to perovskite samples.
Keywords: La(1-)xNixMnO(2.75) perovskite; Effect of Ni doping; Spray pyrolysis; X-ray pattern; PL spectroscopy; Doppler broadening; Emission; Spectroscopy (DBES)